2022
DOI: 10.2217/fmb-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study of Anti-SARS-CoV-2 IgG Antibody Response in COVID-19 Patients up to 6 Months After Infection

Abstract: Introduction: The aim of the current study was to investigate the relationship between lung involvement of SARS-CoV-2 and antibody levels of COVID-19 patients 3 and 6 months from the disease. Methods: A total of 156 participants were divided into two groups, Group 1: lung involvement (LI)-positive and Group 2: LI-negative. Biochemical parameters and anti-SARS-CoV-2 IgG antibody levels were measured. Results: The results showed that mean levels of urea, LDH, CRP, ferritin, neutrophil count and D-dimer were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Finally, 46 studies with 8289 participants (3338 PASC and 4951 controls) were included in our pooled analysis (Table 1). 24–69 These included studies were all peer‐reviewed, published between 2020 and 2023; had data from 28 studies in Resp‐PASC, 10 studies in Neuro‐PASC, 5 studies in Cardio‐PASC, 2 studies in gastrointestinal‐PASC and as only 1 study was in Reno‐PASC. Thirty‐four studies were of cohort design, 11 were case control and 1 cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 46 studies with 8289 participants (3338 PASC and 4951 controls) were included in our pooled analysis (Table 1). 24–69 These included studies were all peer‐reviewed, published between 2020 and 2023; had data from 28 studies in Resp‐PASC, 10 studies in Neuro‐PASC, 5 studies in Cardio‐PASC, 2 studies in gastrointestinal‐PASC and as only 1 study was in Reno‐PASC. Thirty‐four studies were of cohort design, 11 were case control and 1 cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of follow‐up varied among the studies from 2 to 12 months. Majority of the studies reported ICU admission of 4%–100% except a few studies that had mostly mildly COVID‐19 cases in their cohorts during acute infection 28,41,56,68 . Twenty‐four included studies were rated ‘good’ while 22 studies were rated to be of ‘moderate score’ based on the criteria outlined in NOS and Joanna Briggs Institute Critical Appraisal checklist [Supplementary Table and ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation